Aktualisasi Tasawuf Buya Hamka Di Era Postmodern - Nurjana, Siti; Tanjung H., Akbar (Indonesian Journal of Islamic Theology and Philosophy, 2023)
Abstract;Modern Buya Hamka Sufism is very popular, even wrong a reference for Muslims in terms of moral improvement. The attraction of Buya Hamka's thinking lies in his ability to understand the state of society and its needs based on religion, social theory and philosophy. As we already know, Buya Hamka Sufism has greatly contributed to answering the problems of the modern era. This research aims to find out how Buya Hamka Sufism thinks and whether Buya Hamka Sufism can be actualized in the postmodern era. This type of research is library research and is philosophically descriptive. The results of this research are: Firstly, for Buya Hamka Sufism is to cleanse the soul, educate and raise spiritual levels, suppress all greed and gluttony, fight lust especially for self-pleasure. Secondly, Buya Hamka's actualization of Sufism aims to maintain human behavior and reason based on balanced Islamic nature. Humans must work hard to form a good character, avoiding evil and madness. Buya Hamka's Sufism thoughts that must be actualized in the postmodern era are the Concept of Tauhid, the Concept of Zuhud and the Concept of Tawakal and Qona'ah.Keywords:Buya Hamka; Postmodern Era; Sufism. Abstrak;Tassawuf modern Buya Hamka sangat populer, bahkan menjadi salah satu referensi bagi umat islam dalam hal peningkatan moral. Daya tarik pemikiran Buya Hamka terletak pada kemampuannya dalam memahami keadaan masyarakat dan kebutuhannya berdasarkan agama, teori sosial dan juga filsafat. Sebagaimana yang sudah kita ketahui, bahwa tasawuf Buya Hamka sangat berkontribusi dalam menjawab persoalan-persoalan di era modern. Penelitian ini bertujuan untuk mengetahui bagaimana pemikiran tasawuf Buya Hamka dan apakah tasawuf Buya Hamka bisa diaktualisasikan di era postmodern. Jenis penelitian ini adalah kepustakaan (Library Research) dan bersifat deskriptif filosofis. Hasil dari penelitian ini adalah: Pertama Bagi Buya Hamka Tasawuf adalah membersihkan jiwa, mendidik dan menaikkan taraf spiritual, menekan semua keserakahan dan kerakusan, melawan hawa nafsu terlebih untuk kesenangan diri. Kedua aktualisasi tasawuf Buya Hamka bertujuan untuk mempertahankan perilaku dan akal manusia berdasarkan fitrah Islam yang seimbang. Manusia harus bekerja keras untuk membentuk karakter yang baik, menghindari kejahatan dan kegilaan. Pemikiran tasawuf Buya Hamka yang harus diaktualisasikan di era postmodern yaitu Konsep Tauhid, Konsep Zuhud serta Konsep Tawakal dan Qona’ah.Kata Kunci:   Buya Hamka; Era Postmodern; Tasawuf.